Construction of Sexual Identity and Expression of Semarang Adolescents in the Global Economy: A City Ethnographic Adolescent Approach - Wicaksono, Harto; Putri, Noviani Achmad; Fatimah, Nurul (KOMUNITAS: International Journal of Indonesian Society and Culture, 2017)
Liminal identity is a problem faced by adolescence. Liminal events occur due to the reluctance of parents to share adolescent experiences with teenagers in the family. In addition to the transition period, the most noticeable development in adolescence is its physical growth. Physical growth is accompanied by an active hormone that influences the curiosity of adolescents about physical changes, psychological, and biological desires. This study aims to understand the construction of identity and sexual expression of adolescents in Semarang. This research employed descriptive qualitative research. The results of the study indicate that an inappropriate distribution of adolescents’ curiosity brings great consequences during adolescence period. Many adolescents express themselves by having sex outside of marriage and other sexual behaviors. This occurs as a result of wrong association and inaccurate distribution of curiosity. Misconceptions of adolescent behavior also happen due to misconceptions and miss-adaptation of the environment. The behavior is heavily influenced by their environment where they grow and develop, especially in the urban environments which are very complex due to global dynamics.